Introjection And Autopilot Self Posthuman Melancholia In Kazuo Ishiguro’s Klara And The Sun - Selvakumari K, Celin; John, D. Wilfin (Journal of Neonatal Surgery, 2025)
The given paper is going to analyse the notions of introjection and the autopilot self in Klara and the Sun by Kazuo Ishiguro. It combines the psychoanalytic theory like introjection and melancholia with the theory of post humanity, examining the presentation of subdued sorrow by Ishiguro. In taking something in externally on an idea, an object or value and incorporating into itself, is introjection. The autopilot self refers to the lifestyle of following habits, routines, and rules that are imposed by technology more or less like acting out of a script. This paper assumes that Klara and the Sun represent the phenomenon of posthuman melancholy, a state of human beings and robots suffering losses that become impossible to overcome. Such losses include lost futures, lost idea of humanity, and broken relationships. Such losses are coped with by people through introjection and autopilot programs. Ishiguro develops this sadness in two instances: by having an impersonal, procedural narrative voice to non-hypocritically document the events; and by narrating a story about looking after others whereby the loss, is shared between individuals and AI. The methodological framework used in the paper is the trauma studies, memory and recognition research and psychoanalytic theory. Psychoanalysis is a method of interpreting and not a claim of clinical fact. Overall, the paper indicates that Ishiguro is not merely making some predictions about the future of technology. He is also seeking to understand how narratives, networks, and collaborations can assist societies to manage crises. He is also demonstrating how grieving is deferred in a human and AI co-existing world..